NILAI-NILAI ETIKA KOMUNIKASI ANAK DALAM QS. AL-ISRA' [17]: 23 PERSPEKTIF TAFSIR AL-MARAGHI DAN TAFSIR AL-AZHAR - Muktia, Dinda Meilina; Fendi, Fendi; Ulfiyatin, Anis; Rofi'i, Muhammad Arwani (Jurnal Al I'jaz, 2024)
This study examines the values of children's communication ethics towards parents as mentioned in QS. al-Isra’ [17]: 23, comparing the interpretations of Tafsir al-Maraghi and Tafsir al-Azhar. This topic is intriguing because both are contemporary tafsir works, authored by scholars with differing backgrounds, offering unique insights into the verse. The question is how the two interpretations reflect the concept of filial piety in the context of children's communication ethics. The study employs a library research method with a comparative approach. The findings reveal significant differences, where Tafsir al-Maraghi emphasizes that blessings and protection from Allah accompany children who honor their parents, while Tafsir al-Azhar highlights that serving parents is the second obligation after worshiping Allah. Differences in the structural organization of the tafsir works are also noted. This research provides a detailed comparative analysis of communication ethics in the context of filial piety.